2003
DOI: 10.1074/jbc.m208352200
|View full text |Cite
|
Sign up to set email alerts
|

LL5β Is a Phosphatidylinositol (3,4,5)-Trisphosphate Sensor That Can Bind the Cytoskeletal Adaptor, γ-Filamin

Abstract: We identified a potential phosphatidylinositol (3,4,5)-trisphosphate (PtdIns(3,4,5)P 3 ) binding pleckstrin homology domain in the data bases and have cloned and expressed its full coding sequence (LL5␤). The protein bound PtdIns(3,4,5)P 3 selectively in vitro. Strikingly, a substantial proportion of LL5␤ became associated with an unidentified intracellular vesicle population in the context of low PtdIns(3,4,5)P 3 levels produced by the addition of wortmannin or LY294002. In addition, expression of platelet-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 31 publications
(25 reference statements)
2
62
0
Order By: Relevance
“…ERC1a interacts with LL5b (encoded by PHLDB2), a member of the LL5 family of adaptor proteins with a pleckstrin homology (PH) domain, which also includes LL5a (encoded by PHLDB1) and different splice variants. LL5b is part of a stable cortical platform at the periphery of the cell (Paranavitane et al, 2003;Lansbergen et al, 2006;Hotta et al, 2010;Takabayashi et al, 2010). Here, we found that ERC1a and LL5 proteins are needed, together with liprin-a1, to stabilize the edge of migrating cells and for the internalization of active integrins.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…ERC1a interacts with LL5b (encoded by PHLDB2), a member of the LL5 family of adaptor proteins with a pleckstrin homology (PH) domain, which also includes LL5a (encoded by PHLDB1) and different splice variants. LL5b is part of a stable cortical platform at the periphery of the cell (Paranavitane et al, 2003;Lansbergen et al, 2006;Hotta et al, 2010;Takabayashi et al, 2010). Here, we found that ERC1a and LL5 proteins are needed, together with liprin-a1, to stabilize the edge of migrating cells and for the internalization of active integrins.…”
Section: Introductionmentioning
confidence: 73%
“…To further dissect the role of liprin-a1 in cell motility, we have looked for relevant liprin-a1-interacting partners. Here, we have identified the adaptor proteins ERC1 (ELKS/Rab6-interacting/CAST family member 1) (Hida and Ohtsuka, 2010;Südhof, 2012) and LL5 (Paranavitane et al, 2003;Kishi et al, 2005) as important co-players, with liprin-a1, in the regulation of tumor cell migration and invasion. The ERC family (Nakata et al, 1999;Monier et al, 2002;Deguchi-Tawarada et al, 2004) includes ERC2, and two ERC1 isoforms, the brainspecific ERC1b and the widely expressed ERC1a (ELKSe) (Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…TMEM16A is predicted to be associated with the cell membrane. PHLDB2 is a 160 kDa protein that has, in particular, a C-terminal Pleckstrin homology domain that binds phosphatidylinositol (3,4,5)-triphosphates (Dowler et al, 2000;Paranavitane et al, 2003). The overexpressed sequence we detected lacks exon 25 (data not shown).…”
Section: Genes and Processesmentioning
confidence: 78%
“…PHLDB2 codes for a 160 kDa protein with a unique spectrin repeat and a C-terminal Pleckstrin homology domain (Paranavitane et al, 2003). Using RT-QPCR, we found that PHLDB2 is overexpressed in 10/12 HNSCC (six-fold on average, Figure 3b).…”
Section: Pcr-dd and Validation By Reverse Northern Hybridizationmentioning
confidence: 95%
“…It is tempting to speculate that by concentrating KANK1 at the FA rims, talin1 helps to 'nucleate' CMSC assembly, which can then propagate to form large structures surrounding FAs ( Figure 6B). Additional membrane-bound cues, such as the presence of PIP3, to which LL5b can bind (Paranavitane et al, 2003), can further promote CMSC coalescence by increasing concentration of CMSC players in specific areas of the plasma membrane. This model helps to explain why the CMSC accumulation at the cell periphery is reduced but not abolished when PI3 kinase is inhibited (Lansbergen et al, 2006), and why the clustering of all CMSC components is mutually dependent.…”
Section: Discussionmentioning
confidence: 99%